Teacher’s belief of metacognitive reading strategies and awareness in reading classrooms - Mofreh, Samah Ali Mohsen; Salem, Sultan; Wei, Teoh Yi (American Journal of Education and Learning, 2024)
While studies on students’ application of reading strategies have gained prominence, there is a paucity of research on teachers. The study aims to investigate how teachers’ beliefs about metacognitive reading strategies impact their metacognitive awareness in reading classrooms. The samples involved 82 teachers from public secondary schools. This study used a quantitative research design. Research findings demonstrated that teachers significantly believed in and used metacognitive reading strategies, whereas a small number of teachers believed in them but did not implement them. The result of this study indicated that teachers possessed high metacognitive awareness levels while teaching reading comprehension. Analysis underscored the significance of implementing metacognitive reading strategies through a series of implications and suggestions. While some teachers believed in metacognitive reading strategies but did not use them, this study found that teachers believed in and employed them. Additionally, the study indicated that teachers exhibited high levels of metacognitive awareness during reading comprehension instruction, suggesting a strong understanding of their cognitive processes. Based on these results, the study suggests that reading classrooms should gradually use metacognitive reading strategies while taking into account the Malaysian English as a Second Language (ESL) context and traditional teaching methods. The implications of this research underscore the importance of fostering teachers’ metacognitive awareness and strategically applying reading strategies to enhance student learning outcomes.